A Description of The Motivation 3 In 1 Training Participants of Safety Pin Stitching at Balai Diklat Industri Padang - Rismawati Rismawati; Syuraini Syuraini (Universitas Negeri Padang, 2021)
This research was motivated by the low motivation of the participants in participating in the 3 in 1 embroidery pin training at the Padang Industrial Education and Training Center. The goal is to see a picture of the motivation of the participants in following the pinhead embroidery training. This type of research is quantitative with a descriptive approach. The number of respondents in this study was 40 people consisting of training participants for pinhead embroidery training generation II and XIII. The data collection technique used a questionnaire. The data analysis technique uses the percentage formula. The results of this study indicate that the motivation to follow the training participants of the 3 in 1 head embroidery training is still low, namely 71% for 40 respondents.